The geographical foundations of cultural identity in contemporary Lublin - Rodzoś, Jolanta (Institute of Archaeology Rzeszów University, 2012)
A city’s identity should be understood in terms of a set of characteristic features that distinguish it from any other city and underscore its uniqueness. Such unique identity is defined by several factors such as urban landscape, architecture, natural environment, economy and public life. Uniqueness can be achieved either through unmistakable landmarks and phenomena, or through a peculiar combination of objects, not necessarily unique in themselves. Uniqueness may be reflected in the city’s physiognomy, its urban landscape, the specific character of individual sights, as well as people’s awareness, their behaviour and different systems of values. Determining the city’s identity is a long-term, historic process. In the case of Lublin, the geographical conditions that shape the city’s cultural identity are very characteristic. The dynamic landscape and the presence of three river valleys have resulted in a specific spatial display and urban planning. This concerns both older and newer districts. Said conditions are all reflected in Lublin’s urban landscape, green areas arrangement, transport routes, and many other elements. The city is located in a peripheral, agricultural region, which translates into social structure, different systems of values of the city’s inhabitants, as well as into the city’s economy, which inextricably linked with the agricultural character of the Lubelszczyzna region.
Geograficzne podstawy tożsamości kulturowej współczesnego Lublina
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Archaeology subjects::Archaeology; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Archaeology subjects::Archaeology, medieval; Lublin; cultural identity; geographical foundations; historic process; urban landscape; urbanization